Volunteer Finder Application / Muhammad Imran Naim … [et al.] - Naim, Muhammad Imran; Sulaiman, Muhammad Shaiful; Amir Shariffuddin, Amni Nur Syarah; Syahril Affaddy, Arryna Fareeha; Mohamad Salman, Nurun Nabahatil Adawiyah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The proposed app aims to serve as a conduit between people with disabilities and volunteers who can help them with shopping for items. This application is modeled after today’s wellknown delivery apps but uses volunteer networks and location-based services for people who require immediate assistance within the area. Users may customize delivery hours, create shopping lists, and specify their preferences to the app’s layout. Following background checks and development, volunteers can browse for local supermarket assistance requests according to their area and availability. The application enables smooth communication between users and their respecting volunteers by providing real-time updates on shopping progress and messaging services. Through the utilization of modern technology and community participation, this application seeks to improve accessibility for those in need.